Role of Mitochondrial Glycerol-3-Phosphate Dehydrogenase in Metabolic Adaptations of Prostate Cancer - Pecinová, Alena; Alán, Lukáš; Brázdová, Andrea; Vrbacký, Marek; Pecina, Petr; Drahota, Zdeněk; Houštěk, Josef; Mráček, Tomáš (Cells, 2020)
Prostate cancer is one of the most prominent cancers diagnosed in males. Contrasting with other cancer types, glucose utilization is not increased in prostate carcinoma cells as they employ different metabolic adaptations involving mitochondria as a source of energy and intermediates required for rapid cell growth. In this regard, prostate cancer cells were associated with higher activity of mitochondrial glycerol-3-phosphate dehydrogenase (mGPDH), the key rate limiting component of the glycerophosphate shuttle, which connects mitochondrial and cytosolic processes and plays significant role in cellular bioenergetics. Our research focused on the role of mGPDH biogenesis and regulation in prostate cancer compared to healthy cells. We show that the 42 amino acid presequence is cleaved from N-terminus during mGPDH biogenesis. Only the processed form is part of the mGPDH dimer that is the prominent functional enzyme entity. We demonstrate that mGPDH overexpression enhances the wound healing ability in prostate cancer cells. As mGPDH is at the crossroad of glycolysis, lipogenesis and oxidative metabolism, regulation of its activity by intramitochondrial processing might represent rapid means of cellular metabolic adaptations.
Keywords: Prostatic Neoplasms; HEK293 buňky; transfekce; mitochondrie; Transfection; lidé; mužské pohlaví; glycerolfosfátdehydrogenasa; Male; Cell Line, Tumor; Mitochondria; HEK293 Cells; nádory prostaty; nádorové buněčné linie; Glycerolphosphate Dehydrogenase; Humans